2019
DOI: 10.3390/foods8080285
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Crystalline Carotenoids in Carrot Concentrate Powders: Effects of Drying Technology, Carrier Material, and Antioxidants

Abstract: Coloring concentrates of carotenoid-rich plant materials are currently used in the food industry to meet the consumer’s demand for natural substitutes for food colorants. The production of shelf-stable powders of such concentrates comes with particular challenges linked to the sensitivity of the active component towards oxidation and the complexity of the composition and microstructure of such concentrates. In this study, different strategies for the stabilization of crystalline carotenoids as part of a natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
9
0
2
Order By: Relevance
“…More generally, our data indicated that carotenoid stability over time (90 days storage) was lower in the powders than in the emulsions. The porous structure of the powder may favor oxygen diffusion within the sample negatively affecting carotenoids shelf-life stability [73][74][75].…”
Section: Effect Of Storage Conditions On Carotenoid Shelf-life Stability and Degradation Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…More generally, our data indicated that carotenoid stability over time (90 days storage) was lower in the powders than in the emulsions. The porous structure of the powder may favor oxygen diffusion within the sample negatively affecting carotenoids shelf-life stability [73][74][75].…”
Section: Effect Of Storage Conditions On Carotenoid Shelf-life Stability and Degradation Kineticsmentioning
confidence: 99%
“…More generally, our data indicated that carotenoid stability over time (90 days storage) was lower in the powders than in the emulsions. The porous structure of the powder may favor oxygen diffusion within the sample negatively affecting carotenoids shelf-life stability [73][74][75]. Table reports the correlation coefficient (r 2 ), the degradation rate constant (k), and half-life time (t1/2) values of carotenoids in TO, TO/CD emulsions, and powders stored at 25 and 4 °C, in the dark.…”
Section: Effect Of Storage Conditions On Carotenoid Shelf-life Stability and Degradation Kineticsmentioning
confidence: 99%
“…For this purpose, various stabilizing methods were checked, such as oxygen-free storage, freeze and spray drying or different additives (gum Arabic, maltodextrin, modified starch, sodium ascorbate and tocopherols). All methods showed low carotenoid loss, with less than a 5% loss of carotenoids during the processing stage [52]. These conclusions could facilitate industrial applications of carotenoids and make them more practicable for mass production.…”
Section: Improving the Properties Of Carotenoid Colorantsmentioning
confidence: 64%
“…Carrot concentrates are used to produce powders containing crystalline carotenoids. They were examined by Haas et al [52] for stability during drying and storage. For this purpose, various stabilizing methods were checked, such as oxygen-free storage, freeze and spray drying or different additives (gum Arabic, maltodextrin, modified starch, sodium ascorbate and tocopherols).…”
Section: Improving the Properties Of Carotenoid Colorantsmentioning
confidence: 99%
“…Soya milk blend with pineapple and carrot powder preserved its nutritional and microbial quality (Dauda et al, 2016). Functional carrot concentrate powder rich in carotenoid are currently used in various food industries to meet the consumer's demand for natural substitutes for food colorants (Haas et al, 2019). Soymilk is an aqueous, white, creamy extract produced from soybeans which resembles cow milk both in appearance and consistency.…”
Section: Research Articlementioning
confidence: 99%